Exchange Structure in The United States Presidential Election Debate 2024: Donald Trump and Kamala Harris - Maryam Ulfa; Muhammad Yusuf; Fikry Prastya Syahputra (Talenta Publisher, 2025)
This study analyzes the 2024 U.S. presidential election debate between Donald Trump and Kamala Harris using the Interpersonal Function framework, specifically Exchange Structure (Move) from Systemic Functional Linguistics (SFL). The analysis identifies five Move patterns: